Optimization of Patrol Unit Management Samapta Unit to Prevent Criminal Actions of Motor Vehicle Theft at Police Resort Pemalang - Pangestu, Anggito Yudhistira (Advances in Police Science Research Journal, 2024)
The author raises the final assignment with the problem of "Optimizing the Management of the Samapta Unit Patrol Unit to Prevent Criminal Acts of Theft in the Legal Area of the Pemalang Police". The purpose of writing this final project is to identify the implementation of the Samapta Patrol Unit of the Pemalang Police and identify the management of the Patrol Unit of the Pemalang Police Samapta Unit. This study used a qualitative approach with the type of field research by interviewing informants, observing, and studying documents. In addition, the data used was also obtained from various references such as articles, journal books and online media news that were relevant to the problem variables discussed. This study uses Management Theory and Analysis Theory of Strength, Weakness, Opportunities and Threats (SWOT) as well as several concepts that are relevant to the problem, namely the patrol concept based on Regulation of the Head of the Indonesian National Police Security Maintenance Agency Number 1 of 2017 concerning Patrols. The Pemalang Police Samapta Unit is the backbone of preventive police action in preventing criminal acts in the jurisdiction of the Pemalang Police, especially Curanmor. In the implementation of patrols by the Samapta Patrol Unit of the Pemalang Police, several deficiencies were found in terms of planning, organizing, implementing and monitoring and not in accordance with the Patrol SOP stipulated in Perkabaharkam Number 1 of 2017 concerning Patrols. In addition, there were factors that influenced both internally and externally, making the implementation of patrols by the xvii Pemalang Police Samapta Unit unable to be carried out optimally. On the other hand, to improve the implementation of patrols, it is necessary to have creative breakthroughs in efforts to increase the implementation of patrols.